Potential therapeutics against neurological disorders: Natural products-based drugs - Rauf, Abdur; Rahman, Md. Mominur (Frontiers in Pharmacology, 2022)
Neurodegenerative disorders, which are defined by the breakdown of neurons over time, are affecting an increasing number of people. Stroke, Alzheimer's, Parkinson's, Multiple Sclerosis, Migraine, and Amyotrophic Lateral Sclerosis are just a few examples of brain disorders that have no cure. Besides, there is a huge demand for drugs that can cure the diseases mentioned above because the majority of the medications we use to treat them only alleviate diseases. Different neurological disorders have responded satisfactorily to the pharmacological effects of medicinal plants. Despite the numerous multiple types of plants in the world, only a small number of them have been investigated for neurological disorders. As a result, there are many opportunities in this area for further research on plants and their bioactive chemicals. The search for natural therapeutic alternatives that promote faster healing and adverse effects avoidance has gained popularity in recent years. The aim of this mini-review is to explore some natural products that have strong therapeutic effects on neurodegenerative disorders such as Stroke, Alzheimer’s Disease, Parkinson’s Disease, Multiple Sclerosis, Migraine, Amyotrophic Lateral Sclerosis, and others. We have also shown the safety of natural products to improve their appropriate usage in neurological disorders from recent literature.